Correction of protein oxidative modification with quertinein patients with uronephrolithiasis comorbid with metabolic syndrom - Bilai, S. I.; Білай, Сергій Іванович; Билай, С. И. (My University, 2021)
The aim of the research was to study the effect of quertine on the processes of protein oxidative modification in patients with urate nephrolithiasis comorbid with metabolic syndrome. 118 patients, divided into three groups, were examined and treated. Group 1 (control) included patients with urate nephrolithiasis, who were prescribed traditional therapy. Group 2 (experimental) embraced patients with urate nephrolithiasis comorbid with metabolic syndrome, who were prescribed traditional therapy and generally recognized drugs that correct metabolic disorders. Group 3 (main) involved patients with urate nephrolithiasis comorbid with metabolic syndrome, who received traditional therapy and drugs that correct metabolic disorders. To study the state of protein peroxidation, the indicators of protein oxidative modifications were analysedwith the method designed by E.E. Dubininaet al. The study of indicators in the blood serum was performed before treatment and after 7 days, after 14 days, after 1.5-2 months, after 3-6 months. In patients with urate nephrolithiasis, prooxidant activation was observed in the course of traditional therapy: the level of neutral aldehyde and ketone derivatives as well as of alkaline aldehyde derivatives increased. Patients with urate nephrolithiasis and urate nephrolithiasis comorbid with metabolic syndrome demonstrated the development of oxidative stress, manifested by the accumulation of the content of products of protein oxidative modification. After the treatment with quertine, which contains the aglycone of various plant flavonoid glycosides, a more significant decrease in the indicators of protein oxidative modification was noted comparing to experimental group patients; this indicates the antioxidant properties of quertine. Thus, the use of quertine together with traditional therapy and drugs that affect metabolic disorders, differentiated between uricostatic and uricolytic agents, contributed to the normalization of the content of protein peroxidation products. Метою дослідження було вивчення впливу квертину на про- цеси окисної модифікації білків у хворих на уратний нефролітіаз коморбідний з метаболічним синдромом. Обстежено та проведено лікування 118 пацієнтів, які були розділені на три групи. 1-а група (контрольна) – хворі на уратний нефролітіаз, яким застосовували традиційну терапію. 2-а група (порівняння) – хворі на уратний нефролітіаз коморбідний з метаболічним синдромом, яким застосовували традиційну терапію та загальноприйняті лікарські засоби, які коригують метаболічні порушення. 3-я група (основна) – хворі на уратний нефролітіаз коморбідний з метаболічним синдромом, яким застосовували квертин, традиційну терапію та лікарські засоби, які корегують метаболічні порушення. Для вивчення стану перекисного окиснення білків досліджували показники окисної модифікації білків по методиці Є.Є. Дубініної та співавторів. Дослідження показ- ників дифенілгідрозоніву сироватці крові супроводжувалося: до лікування, через 7 днів, через 14 днів, через 1,5-2 місяців, через 3-6 місяців. У хворих на уратний нефролітіаз протягом лікування традиційною терапією спостерігалася прооксидантна активація – підвищувався рівень альдегідних, кетонових похідних нейтрального характеру, альдегідопохідних лужного характеру. У хворих на уратний нефролітіаз коморбідний з метаболічним синдромом до лікування спостерігався істотний розвиток оксидативного стресу, що проявлялося накопиченням вмісту продуктів окисної модифікації білків. Після проведеного лікування квертином, який містить аглікон багатьох рослинних флавоноїдних глікозидів, було відзначено більш суттєве зниження показників окисної модифікації білків, ніж у хворих групи порівняння, що вказує на антиоксидантні властивості квертину. Таким чином, застосування квертину спільно з традиційною терапією та лікарськими засобами, які впливають на метаболічні порушення, диференційовано урикостатичних та уриколітичних засобів, сприяло нормалізації вмісту продуктів перекисного окиснення білків.
Корекція квертином окисної модифікації білків у хворих на уратний нефролітіаз коморбідний з метаболічним синдромом
Коррекция квертином окислительной модификации белков у больных уратным нефролитиазом коморбидным с метаболическим синдромом
Keywords: quertine; urate nephrolithiasis; metabolic syndrome; protein oxidative modification; квартин; уратний нефролітіаз; метаболічний синдром; окисна модифікація білків